Ensilability and chemical composition of silages made with different mixtures of noni (Morinda citrifolia L.) - Sánchez, Yoandris Pascual; Betancur Hurtado, Cesar; Botello León, Aroldo; Pérez Corría, Kirenia; Ruiz Corrales, Cristina; Martínez Aguilar, Yordan (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (Páginas 3-16).